Novel Silane Crosslinked Chitosan Based Electrospun Nanofiber for Controlled Release of Benzocaine - Naz, Mehwish; Jabeen, Sehrish; Gull, Nafisa; Ghaffar, Abdul; Islam, Atif; Rizwan, Muhammad; Abdullah, Huda; Rasool, Atta; Khan, Shahzad; Khan, Rafi (Frontiers in Materials, 2022)
Nanofibers mats of chitosan (CTS)/polyvinyl alcohol (PVA)/halloysite nanoclay and drug loaded CTS/PVA/halloysite nanoclay//3-glycidyoxypropyl trimethoxysilane were fabricated using the electrospinning method. Electrospun nanofiber samples were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). FTIR confirmed the chemical and physical bonding among ingredients such as CTS, PVA, nanoclay and crosslinker in the nanofibers. SEM images showed the development of uniform nanofibers. The average nanofiber diameter was observed in the range of 50–200 nm. Antimicrobial activity was examined against E. coli and S. aurus bacteria. The results obtained indicated that all nanofiber samples showed significant antimicrobial activity against the Gram-positive as well as Gram-negative bacteria. TGA results indicated that the thermal stability of nanofibers increased with the addition of the crosslinker. The drug release was studied in phosphate buffer saline (PBS) solution (pH 7.4) at 37°C and was released from nanofibers in 2.5 h. Hence, these prepared nanofibers can be used in medication where the drug is required for a long duration.